Antifungal activity and expression patterns of extracellular chitinase and β-1, 3-glucanase in Wickerhamomyces anomalus EG2 treated with chitin and glucan. (September 2017) - Hong, Sin-Hyoung; Song, Yong-Su; Seo, Dong-Jun; Kim, Kil-Yong; Jung, Woo-Jin
Abstract: In this study, the expression patterns of extracellular chitinase and β-1, 3-glucanase from cultured Wickerhamomyces anomalus EG2 treated with chitin, glucan, and chemical chitinase inhibitors (kinetin, caffeine, and acetazolamide) were investigated using SDS-PAGE. Relationship between enzyme expression and antifungal activity from yeast plays a very important role for biocontrol of phytopathoges. To determine antifungal activity against phytopathogens, W. anomalus EG2 was shown to strongly inhibit hyphal growth of Fusarium oxysporum KACC 40032 and Rhizoctonia solani KACC 40111. Slight chitinase activity was observed 12 h after incubation in both PDB and YPD medium without colloidal chitin. The molecular weight of chitinase was approximately 124 kDa β-1, 3-Glucanase isoenzyme (GN1 and GN2) was observed distinctly on SDS-PAGE gels when laminarin was used as a substrate. β-1, 3-Glucanase isoenzyme was not observed when using glucan-containing high polymer complex (GHPC) as a substrate. Production of chitinase from W. anomalus EG2 was inhibited slightly by acetazolamide. Abnormal and cluster-shaped cells of W. anomalus EG2 were observed in both PDB and YPD medium treated with colloidal chitin. These results indicated that W. anomalus EG2 could be applied commercially as a biological control agent of phytopathogens and as a bioinhibitor of yeast cell growth. Highlights: W. anomalus EG2 was shown to strongly inhibit hyphal growth of F. oxysporum and R. solani . Production of chitinase from W. anomalus EG2 was inhibited slightly by acetazolamide. The molecular weight of chitinase was approximately 124 kDa. Abnormal and cluster-shaped cells of W. anomalus EG2 were observed in both PDB and YPD medium treated with colloidal chitin.